2018
DOI: 10.5194/isprs-archives-xlii-3-1215-2018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of RGB-Based Vegetation Indices From Uav Imagery to Estimate Forage Yield in Grassland

Abstract: ABSTRACT:Monitoring forage yield throughout the growing season is of key importance to support management decisions on grasslands/pastures. Especially on intensely managed grasslands, where nitrogen fertilizer and/or manure are applied regularly, precision agriculture applications are beneficial to support sustainable, site-specific management decisions on fertilizer treatment, grazing management and yield forecasting to mitigate potential negative impacts. To support these management decisions, timely and acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 15 publications
2
40
2
3
Order By: Relevance
“…The PPR can distinguish the first (0 kg N/ha) and second (50 kg N/ha) treatment, although it fails to distinguish between the third (100 kg N/ha) and fourth (150 kg N/ha) treatment, similarly to the NGRDI and NDVI. The performance of the NGRDI was similar to the results reported by Lussem et al (2018) on the same test site, but for a different year. Hunt et al (2005) reported a good correlation of the NGRDI to alfalfa, corn and soybean biomass, but observed saturation effects for higher biomass yield, which is similar in this study and can be related to Motohka et al (2010), who observed that RGB-based VIs are limited to certain growing stages.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The PPR can distinguish the first (0 kg N/ha) and second (50 kg N/ha) treatment, although it fails to distinguish between the third (100 kg N/ha) and fourth (150 kg N/ha) treatment, similarly to the NGRDI and NDVI. The performance of the NGRDI was similar to the results reported by Lussem et al (2018) on the same test site, but for a different year. Hunt et al (2005) reported a good correlation of the NGRDI to alfalfa, corn and soybean biomass, but observed saturation effects for higher biomass yield, which is similar in this study and can be related to Motohka et al (2010), who observed that RGB-based VIs are limited to certain growing stages.…”
Section: Discussionsupporting
confidence: 82%
“…Bendig et al 2015, Hunt et al 2005, Jannoura et al 2015. Recent studies deployed UAV-based multispectral or RGB cameras to assess grassland biomass with good results (Lussem et al, 2018;Viljanen et al, 2018). In this contribution we want to evaluate simultaneously acquired RGB-based vegetation indices from a consumer-grade RGBcamera and a well-calibrated narrow-band multispectral camera to estimate dry biomass yield on an experimental grassland field in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Color indices are acquired through algebraic calculation with reflectance values from the R (red), G (green), and B (blue) bands, respectively. While color indices can be used to segment plants from overall image as mentioned above, the main value of color indices is in facilitating the prediction or estimation of biophysical properties of target plants, such as biomass, leaf area index, and yield [67][68][69]. RGB digital cameras have advantages in their high resolution and low price, but the sensors also have limitations in overlapping the red, green, and blue wavelength spectra ( Table 5).…”
Section: Rgb Digital Camerasmentioning
confidence: 99%
“…A multispectral sensor can collect radiation data from spectral bands with almost no overlapping [26,69]. Further, it can include data of near-infrared wavelength.…”
Section: R790mentioning
confidence: 99%
See 1 more Smart Citation